THE ROLE OF HYPERTENSION IN THE DEVELOPMENT OF STRUCTURAL CHANGES IN THE BRAIN AFTER SIMULATION OF HEMORRHAGIC STROKE - Олійник, Т.М.; Савосько, С.І.; Шанта, А.В.; Чайковський, Ю.Б. (World of Medicine and Biology, 2016)
The article describes the results of experimental study devoted to studying the role of hypertension in the development and progression of histological changes in the brain after hemorrhagic stroke. Based on the analysis of histological and morphometric study was found an increase of cerebral edema and neurodegenerative changes in various cellular and anatomical brain formations of hypertensive rats compared to normotensive. Hypertensive rats were observed to have more pronounced apoptosis of neurons in the sensorimotor cortex, glial apoptosis in corpus callosum and the degree of ependymal desquamation into ventricular lumen. Research results confirmed the effect of hypertension on the dynamics of brain edema as a pathogenetic factor of progressive neurodegenerative changes.